1989
DOI: 10.1016/0042-6822(89)90048-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coronavirus JHM variants isolated from wistar furth rats with a viral-induced demyelinating disease

Abstract: Murine hepatitis virus (MHV) can cause neurological disease when inoculated intracerebrally (ic) into mice and rats. Specifically the JHM strain of MHV (MHV-JHM) generally causes an acute encephalitis when inoculated ic into 2-day-old Wistar Furth rats. In contrast, JHM generally produces a chronic demyelinating disease with resulting posterior paralysis when inoculated ic into 10-day-old Wistar Furth rats. In addition, while JHM readily produces a productive infection in a mouse fibroblast cell line (L-2), it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…Studies in a number of laboratories have shown that there is considerable heterogeneity in the size of the S protein of different MHV isolates (Taguchi et al, 1985, 0001-0654 © 1992.SGM 1986Morris et al, 1989;Parker et al, 1989). We have reported that two variant viruses, cl-2 and CNSV with a larger S protein, are preferentially isolated from rat brains and cultured neural cells (Taguchi et al, 1985(Taguchi et al, , 1986.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in a number of laboratories have shown that there is considerable heterogeneity in the size of the S protein of different MHV isolates (Taguchi et al, 1985, 0001-0654 © 1992.SGM 1986Morris et al, 1989;Parker et al, 1989). We have reported that two variant viruses, cl-2 and CNSV with a larger S protein, are preferentially isolated from rat brains and cultured neural cells (Taguchi et al, 1985(Taguchi et al, , 1986.…”
Section: Introductionmentioning
confidence: 99%
“…These animals were inoculated with a mixed virus population that consisted predominantly of virus with a smaller S protein and we believe that variants cl-2 and CNSV become the major population in rat brains because of selective growth in rat neural cells (Taguchi et al, 1985;Matsubara et al, 1991). It has also been reported (Morris et al, 1989) that a virus with a smaller S protein, AT1 If cord virus, was isolated from the central nervous system of rats persistently infected with JHMV. AT1 If cord virus has a lower virulence than the virus with a larger S protein originally inoculated into the rat brains.…”
Section: Introductionmentioning
confidence: 99%
“…Many preclinical glioma models have been reported that are derived by gene targeting in transgenic mice, 4 by carcinogen induction, 5 and by viral infection. 6 Each has drawbacks and restrictions. For example, 4C8 cells from B6D2F1 transgenic mice develop a pattern of necrosis and express glial fibrillary acidic protein (GFAP), but are not very aggressive.…”
mentioning
confidence: 99%
“…Results from previous studies have indicated that the S gene of coronaviruses plays an important role in virulence and pathogenicity (Taguchi et al, 1985 ;Dalziel et al, 1986 ;Fleming et al, 1986 ;Wege et al, 1988 ;Morris et al, 1989 ;Parker et al, 1989 ;LaMonica et al, 1991 ;Wang et al, 1992). Therefore, we investigated whether coronavirus replication in brain tissue of persistently infected Lewis rats results in an accumulation or selection of S gene variants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the S and HE proteins are important determinants for the neuropathogenicity of the virus and for its ability to infect a variety of cell types (Taguchi et al, 1985 ;Morris et al, 1989 ;Parker et al, 1989 ;Wang et al, 1992 ;LaMonica et al, 1991 ;Fazakerley et al, 1992 ;Yokomori et al, 1993). The S protein in particular elicits neutralizing antibodies, binds to cell receptors and causes cell fusion.…”
Section: Jhm-pi Using Rt-pcr Amplification Methods the S Gene Sequenmentioning
confidence: 99%